The Contribution of Majelis Taklim Tastafi in Shaping the Spiritual Dimension of Langsa City Community - Teuku Wildan (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
This study aims to determine the contribution of the majelis taklim Tastafi in shaping the spiritual dimension of the Langsa City community. Participants in the study were 30 members of the majelis taklim Tastafi. The mixed-method approach is used to answer the problem; the quantitative type uses Pearson product-moment, and the qualitative type uses the descriptive-analytical method. The results of the research findings show there is a significant relationship between the activities of the majelis taklim Tastafi in shaping the spiritual dimension of the Langsa City community, indicated by the validity test of the Pearson product-moment correlation data on the activities of the majelis taklim Tastafi and the spiritual dimension, prayer fulfilment fields 0.959, universality 0.954 and connectedness 0.937. The null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) proposed is accepted; namely, there is a positive relationship and a very significant correlation between attending majlis taklim and the spiritual dimension variables. The higher the routine in attending the majelis taklim, the higher the spiritual dimension and vice versa; this is evidenced by the validity of the data with the results of all values ​​​​of the spiritual dimension on Sig ( 2-tailed) was 0.000 (p < 0.01). The formation of the spiritual dimension is seen in the practice of worship, belief, relationship with God and humans, and individual responsibilities in life. Keywords: majelis, contribution, spiritual